2014
DOI: 10.1186/s12862-014-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

Extensive diversity of Rickettsiales bacteria in two species of ticks from China and the evolution of the Rickettsiales

Abstract: BackgroundBacteria of the order Rickettsiales (Alphaproteobacteria) are obligate intracellular parasites that infect species from virtually every major eukaryotic lineage. Several rickettsial genera harbor species that are significant emerging and re-emerging pathogens of humans. As species of Rickettsiales are associated with an extremely diverse host range, a better understanding of the historical associations between these bacteria and their hosts will provide important information on their evolutionary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 51 publications
2
81
1
Order By: Relevance
“…Rickettsiales are obligate intracellular bacteria that colonize a broad range of eukaryotic hosts, including various arthropod and mammalian cells, leeches, nematodes, and cnidarians (9,65). Besides metazoan hosts, diverse protists harbor rickettsial endosymbionts as well (5,9,65). Previous analyses of molecular sequence data as well as our present results reveal that the rickettsial phylogeny is not congruent with the phylogeny of the host organisms, indicating a frequent lateral transfer of rickettsial endosymbionts between phylogenetically distant hosts (9,65).…”
Section: Phylogenetic Identity and Taxonomy Of "Candidatus Finniella"mentioning
confidence: 41%
See 3 more Smart Citations
“…Rickettsiales are obligate intracellular bacteria that colonize a broad range of eukaryotic hosts, including various arthropod and mammalian cells, leeches, nematodes, and cnidarians (9,65). Besides metazoan hosts, diverse protists harbor rickettsial endosymbionts as well (5,9,65). Previous analyses of molecular sequence data as well as our present results reveal that the rickettsial phylogeny is not congruent with the phylogeny of the host organisms, indicating a frequent lateral transfer of rickettsial endosymbionts between phylogenetically distant hosts (9,65).…”
Section: Phylogenetic Identity and Taxonomy Of "Candidatus Finniella"mentioning
confidence: 41%
“…Rickettsiales are obligate intracellular bacteria that colonize a broad range of eukaryotic hosts, including various arthropod and mammalian cells, leeches, nematodes, and cnidarians (9,65). Besides metazoan hosts, diverse protists harbor rickettsial endosymbionts as well (5,9,65).…”
Section: Phylogenetic Identity and Taxonomy Of "Candidatus Finniella"mentioning
confidence: 99%
See 2 more Smart Citations
“…The gltA locus of Rickettsia was amplified from Eucampsipoda madagascarensis and Penicillidia leptothrinax samples. Classification using BLASTx showed that the obtained gltA sequences showed little homology to known species of Rickettsia, with the strongest match showing 90% identity to gltA from Rickettsia raoultii, a bacterium identified in hard ticks from China (46). In addition, a 1,350-bp fragment of the 16S gene of Rickettsia was amplified from Eucampsipoda madagascarensis.…”
Section: Resultsmentioning
confidence: 99%